ANALYTICAL METHOD EVELOPMENT AND VALIDATION FOR ANTI ASTHAMATIC DRUG OXYMETAZOLINE HYDROCHLORIDE IN NASAL SPRAY FORMULATIONS BY RP-HPLC - Kulkarni, Pankaj N; Dodake-Supekar, Alaknanda M; Nipte, Amol S; Jadhav, Chetan K; Gill, Charansingh H. (Journal of Drug Delivery and Therapeutics, 2019)
A new, simple, accurate and economic reverse-phase HPLC method has been developed for quantification of Oxymetazoline Hydrochloride in nasal spray formulations. This developed method has been validated according to International Conference on Harmonization (ICH) guideline with respect to system suitability, specificity, precision, linearity, accuracy, and robustness. An isocratic condition of mobile phase Phosphate buffer (pH 3.0): Acetonitrile in a ratio of 60:40, v/v at a flow rate of 1.0 mL/minute over RP C18 (octadecylsilane (ODS), 250 × 4.6 mm, 5 µm, ECLIPSE X DB C-18) column at ambient temperature was maintained. This method is specific and showed excellent linear response with correlation coefficient (R2) values of 0.999, which was within the limit of correlation coefficient (R2 0.995). A  simple  and accurate reversed-phase  HPLC  method  for  the  analysis  of  Oxymetazoline Hydrochloride in  nasal spray formulations was developed and validated successfully.